Classification using the C4.5 Algorithm in Predicting Students Organizational Status Amikom University Yogyakarta - Neni Firda Wardani Tan; Kusnawi Kusnawi (Sistemasi: Jurnal Sistem Informasi, 2022)
Participation in an organization as a college student is an important way to self-improvement. This research analyzes students' learning in an organization and whether the student is active or not active in an organization using the Decision Tree C4.5 algorithm. Attributes analyzed were out-of-campus organization, previous organization experience, public speaking, problem-solving, confidence level, and personality. From a question from propagating on October 2021, the researcher collect 203 raw data, with 167 processes ones that were used in this research. The test conducted results in a tree or the decision tree that could be used to decide how active a student is in an organization. The accuracy value of this test using cross-validation resulted in a score of 59.27% or in comparison to the data training: data testing of 4:1 or 80%: 20%.